PEMBERIAN BERBAGAI DOSIS PROBIOTIK PADA PAKAN TERHADAP PERTUMBUHAN, DAN FCR IKAN BANDENG (Chanos chanos) DENGAN SISTEM POLIKULTUR - Tri Rahayu Ningsih; Endah Sri Redjeki; Sa’idah Luthfiyah (Universitas Muhammadiyah Gresik, 2018)
Milkfish is including commodities that easy to cultivated and has high interest comsumption. The technology that support cultivation of milkfish still weak in optimalyze the growth of it. Research design of this study is group randomized design (RAK). The purpose of this study is to analyze the appropriate dose of growth variable, and FCR of milkfish by using policulture system. This study using 4 treatment and 3 repeatition by different probiotic dose of treatement. Treatment P0 (control), P1 (giving probiotic 8 ml/kg of feed), P2 (giving probiotic 10 ml/kg of feed), P3 (giving probiotic 12 ml/kg of feed). Variable that observed by growth, and FCR of milkfish. The result of ANOVA analysis shows that the difference is very real of variable of daily growth rate, absolute weight, FCR of milkfish, and SGR of seaweed. Varibale that shows a difference next by BNT further testing, so that the best treatment as known is P2 (giving probiotic 10 ml/kg of feed). Giving of dose variety of feed gives real difference toward growth. Growth is indicated by daily growth rate and absolute weight. Giving P2 of probiotic (giving probiotic 10 ml/kg of feed) able to apply to cultivators so that press the value of feed conversion ratio.